Indonesia's Russia-Ukraine war stance and the Global South: between solidarity and transactionalism - Sebastian, Leonard C. (2024)
How does Indonesia's positioning in relation to the Russia-Ukraine war shape the country's view on global order? President Joko Widodo or Jokowi visited both Russia and Ukraine in June 2022 in the pretext of brokering peace between the two countries. Indonesia though refrained from taking sides in the Russo-Ukraine war. During his visit, Jokowi stressed the necessity for the war to end. Equally important but of greater significance was his emphasis on the importance of re-establishing the global supply chains of food, fertiliser, and energy. The resumption of these global supply chains would safeguard Indonesia's economic stability. We argue that domestic determinants were influential in moulding Indonesia's policy position which aimed at shaping Global South solidarity into one privileging Indonesia's transactional stance. The country's economic interests were a key driver shaping its response to the Russia-Ukraine war. Furthermore, Indonesia's approach towards the war reflected ‘varied consequentialism’ as cost–benefit analysis plays a significant role.